International Association of Athletics Federations Consensus Statement 2019: Nutrition for Athletics - Burke, L. M.; Castell, L. M.; Casa, D. J.; Close, G. L.; Costa, R. J. S.; Desbrow, B.; Halson, S. L.; Lis, D. M.; Melin, A. K.; Peeling, P.; Saunders, P. U.; Slater, G. J.; et al. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The International Association of Athletics Federations recognizes the importance of nutritional practices in optimizing an Athlete`s well-being and performance. Although Athletics encompasses a diverse range of track-and-field events with different performance determinants, there are common goals around nutritional support for adaptation to training, optimal performance for key events, and reducing the risk of injury and illness. Periodized guidelines can be provided for the appropriate type, amount, and timing of intake of food and fluids to promote optimal health and performance across different scenarios of training and competition. Some athletes are at risk of relative energy deficiency in sport arising from a mismatch between energy intake and exercise energy expenditure. Competition nutrition strategies may involve pre-event, within-event, and between-event eating to address requirements for carbohydrate and fluid replacement. Although a "food first" policy should underpin an Athlete`s nutrition plan, there may be occasions for the judicious use of medical supplements to address nutrient deficiencies or sports foods that help the athlete to meet nutritional goals when it is impractical to eat food. Evidence-based supplements include caffeine, bicarbonate, beta-alanine, nitrate, and creatine; however, their value is specific to the characteristics of the event. Special considerations are needed for travel, challenging environments (e.g., heat and altitude); special populations (e.g., females, young and masters athletes); and restricted dietary choice (e.g., vegetarian). Ideally, each Athlete should develop a personalized, periodized, and practical nutrition plan via collaboration with their coach and accredited sports nutrition experts, to optimize their performance